The Athletic Identity and Level of Optimism of Selected University of Santo Tomas Institute Student-Athletes during the Covid-19 Pandemic - Chuateco, Clinyl Mae; Cervantes, Dominic; Lipasana, Daisy Grace; Mosqueda, Anjelica Devi; Requinton, Jaron; Dimatulac, Olivia (INSPIREE: Indonesian Sport Innovation Review, 2022)
The  purpose  of  the study. The COVID-19 pandemic has impacted sporting events, which led to the cancellation of games and student-athletes being isolated at home and conducting their training online. The study looked at how student-athletes view themselves and their levels of optimism before and during the pandemic. Materials and methods. The study is a descriptive quantitative research that adapted the constructs of the Athletic Identity Measurement Scale (AIMS) and Revised Life Orientation Test (LOT-R). Slovin’s formula and stratified random sampling were used to select the respondents. Google Form was used to gather data on the 154 UST-IPEA student-athletes. For data analysis, Microsoft Data Analysis ToolPak was used as statistical software. Results. The results show that the factors of Level of Optimism, namely: Gender, Typology of Sports, and Competitive Level, do not affect the student-athletes Level of Optimism before and during the COVID-19 pandemic. Meanwhile, the factors of Athletic Identity, namely: Gender, Year Level, and Socioeconomic Status, do not affect the student-athletes’ Athletic Identity before the COVID-19 pandemic. However, one factor that affects the student-athletes’ Athletic Identity during the COVID-19 pandemic is the Typology of Sports. To sum up, the Athletic Identity and Level of Optimism possess a weak correlation. Conclusions. . Based on the results of the study, it is concluded to regularly monitor the student-athletes’ Athletic Identity and Level of Optimism by taking the Athletic Identity Measurement Scale (AIMS) by Brewer & Cornelius (2001) and Revised Life Orientation Test (LOT-R)).